Assessment of the extent and monetary loss in the selected public hospitals in Jimma Zone, Ethiopia: expired medicine perspectives - Getahun, Habtamu; Belew, Sileshi; Hasen, Gemmechu; Tefera Mekasha, Yesuneh; Suleman, Sultan (Frontiers in Medicine, 2024)
Medicine plays a crucial role in the field of healthcare as a therapeutically significant pharmaceutical product. By effectively preventing illnesses, medicine has the power to save countless lives and improve the quality of life for people worldwide. However, despite hospitals' efforts to provide medical care to patients, a significant issue arises from the substantial amount of drugs that go unused due to expiration dates. This problem is particularly prevalent in resource-limited countries like Ethiopia, where the pharmaceutical supply system fails to adequately address the issue of expired drugs in public hospitals, leading to an unsatisfactory situation. Hence, the objective of this study was to assess the economic impact and volume of expired medicines in the selected public hospitals in Jimma Zone, Southwestern Ethiopia. A hospital-based cross-sectional study was designed to assess the economic impact and volume of expired medicines available in the public hospitals in Jimma Zone. All available hospitals that fulfilled the EFDA guidelines were included. The medication expiration rate was calculated by dividing the total monetary value of expired medicines in a year by the total value of medicines received in the same year multiplied by 100. Then, the collected data was cleared, filtered, coded, and quantitatively analyzed using the Microsoft Excel 2010 version. The average medicine waste rate was 4.87% in the fiscal year of 2019/2020 and 2020/2021 in Jimma Zone public hospitals worth 32,453.3 US. Additionally, the facility wasted an estimated of 2711.44 US on the disposal of expired medicines. The expiration of medicines has been linked to several issues, including near-expiry, irrational prescribing practices, and weak participation of clinicians in medicine selection and quantification of the facility. Additionally, only two hospitals had relatively good storage and handling practices. Overall,the expiration rate of medicines in the public hospitals in Jimma Zone was greater than the allowed level of 2%. In order to use health budgets and pharmacologically relevant medications efficiently, it is therefore necessary to conduct a comprehensive study based in a regional hospital to evaluate the volume and economic impact of expired medications.